1997
DOI: 10.1074/jbc.272.50.31837
|View full text |Cite
|
Sign up to set email alerts
|

Variant Exons v6 and v7 Together Expand the Repertoire of Glycosaminoglycans Bound by CD44

Abstract: Isoforms of the glycoprotein CD44 are cell surface receptors for the glycosaminoglycan hyaluronate. They have been implicated in many biological processes, but their function in these is poorly understood and cannot be explained solely by hyaluronate binding. In the present work we examine the ligand binding properties of alternatively spliced CD44 variant isoforms which are functionally involved in the immune system, embryonic development, and tumor behavior. We show that these isoforms bind directly to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…CD44 containing exons v6 and v7 in the one CD44 molecule have an increased repertoire of glycosaminoglycan ligands. 32 Neither exon expressed alone has this effect. These results emphasise the importance of the exon combinations rather than the effect of individual exons in the function of CD44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 containing exons v6 and v7 in the one CD44 molecule have an increased repertoire of glycosaminoglycan ligands. 32 Neither exon expressed alone has this effect. These results emphasise the importance of the exon combinations rather than the effect of individual exons in the function of CD44.…”
Section: Discussionmentioning
confidence: 99%
“…7 The insertion of variant exons into the membrane proximal region can modify the adhesive function of CD44 and could therefore modify the interactions between hematopoietic progenitors and the bone marrow stroma. 22,32 Exons v8-v10 have been detected in normal hematopoietic cells. 12,23 In addition to exons v8-v10 we have detected mRNA containing exons v3 and v6 alone in normal resting bone marrow mononuclear cells, peripheral blood lymphocytes and CD34 + progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion protein containing the F-actin binding domain rather enhanced c-Met signaling. Note, however, that c-Met activa- Figure 3B), a fusion construct between CD44v6 and ezrin lacking the last 34 C-terminal amino acids (ez⌬ABD), or a CD44v6 full length construct (pGKs6; Sleeman et al, 1997) together with HA-Erk and detection of HGF induced HA-Erk phosphorylation. The -fold induction by HGF is indicated.…”
Section: F-actin Organizes Ras Activationmentioning
confidence: 99%
“…Expression vectors containing rat CD44v6 fused to full-length or truncated rat ezrin: The CD44 part was amplified by polymerase chain reaction (PCR) covering the 5Ј-untranslated region to the transmembrane domain from the pGKs6 vector (Sleeman et al, 1997). The primers used were CGCGACCCTTT-TCCAGAGGCTACTAGATCCTTTGG TTTCATCCTGCACATCATGG and GTCTGCATTGCTGTCAACAGTAGGAGG AAGCAGACGTAACGACAGT-TGTCATCCTCCTTCCTTTGGAAAC.…”
Section: Constructsmentioning
confidence: 99%
“…It has also been shown that alternative splicing can modulate the affinity of CD44 for hyaluroare spliced out encode the most common and widely expressed 85-kDa isoform (CD44s). Further diversity is introduced into nate [16Ϫ18] and induce binding of the protein to other GAF through the hyaluronate-binding motif [18]. Furthermore, an anthe CD44 family of proteins by O-linked and N-linked sugar tibody specific for CD44 variant isoforms containing an exonmodifications and by glycosaminoglycan (GAG) additions [2].…”
mentioning
confidence: 99%